Multidrug resistance and extended-spectrum beta-lactamase producing Gram-negative bacteria from three Referral Hospitals of Amhara region, Ethiopia - Moges, Feleke (Ann Clin Microbiol Antimicrob, 2021)
BACKGROUND: Multidrug resistance (MDR), extended-spectrum beta-lactamase (ESBL) and carbapenemase-producing Gram-negative bacteria (GNB) has become a public health threat worldwide. This threat is worse in developing countries where there is high infectious disease burden and spread of antimicrobial resistance co-exist. The aim of the present study was, therefore, to assess MDR, ESBL and carbapenemase producing GNB from patients attending three selected referral hospitals in Amhara region. METHODS: A cross-sectional study was conducted from December 2017- April 2018 at the University of Gondar Comprehensive Specialized Hospital, Dessie Referral Hospital and Debre Markos Referral Hospital of Amhara national regional state. A total of 833 study subjects were recruited using a convenient sampling technique. Clinical samples such as blood, urine, stool, wound, abscess, ear discharge, nasal discharge, cervical discharge and body fluid specimens were aseptically collected. Culturing for identification of bacteria and determination of drug susceptibility testing were done following standard microbiological techniques. Selected MDR isolates were phenotypically assessed for ESBL and carbapenemase production. RESULTS: Of the 833 clinical samples cultured for bacterial growth, 141 (16.9%) were positive for GNB. The most common GNB identified were E. coli 46 (32.6%), Klebsiella spp. 38 (26.5%) and Proteus spp. 13 (9.2%). The overall MDR prevalence was 121 (85.8%). Among the total isolates, 137 (97.2%) were resistant to ampicillin followed by cotrimoxazole 115 (81.6%), amoxicillin-clavulanic acid 109 (77.3%), cefixime 99 (70.2%), cefepime 93 (66.0%) and tetracycline 91 (64.5%). The extended-spectrum beta-lactamase producing GNB were 69/124 (55.6%). Of which Klebsiella spp. 19 (15.3%) and E. coli 17 (13.7%) were common ESBL producers. Carbapenemase-producing isolates were 8/51(15.7%). Of which Enterobacter, Klebsiella and E. coli were common carbapenemase producers. CONCLUSION AND RECOMMENDATION: Multi-drug resistance and ESBL producing isolates in the present study were high. E. coli and Klebsiella spp. were the most common ESBL producing GNB. Klebsiella spp., Enterobacter spp., E. coli and Citrobacter spp. were typical carbapenemase-producing isolates. Continuous monitoring, antibiotic stewardship and molecular detection of the gene responsible for drug resistance are important means to reduce the spread of drug-resistant pathogens.